Measurement of financial assets and financial liabilities: ifrs/ us gaap comparison - Yetişer, Ebru (My University, 2006)
FİNANSAL VARLIKLARI VE FİNANSAL YÜKÜMLÜLÜKLERİ ÖLÇÜMLEME: UFRS/ AGKGM KARSILASTIRMASI Degisik ülkelerdeki finansal raporlama kuralları arasındaki farklılıklar muhasebede karmasıklıga yol açmaktadır.Uluslararası küresellesme için, muhasebedeki farklar asgariye indirilmeli ve uyumlastırılma gerçeklestirilmelidir. Dünyadaki çogu ülkede yerel standartlar, UFRS veya AGKGM_’ne dayanmaktadır. Uygun bir zaman dilimi içerisinde tek bir grup küresel muhasebe standardı olusturmanın yolu UFRS- AGKGM_ yakınsaması üzerinde çalısmaktır. Bu yakınsama kendi yerel genel kabul görmüs muhasebe ilkelerini kullanmaya devam eden ülkeleri etkileyecektir. Yakınsama projesinin ana engeli UFRS ve AGKGM_’nin temelde iki farklı finansal raporlama sistemi olmasıdır. AGKGM_ islem ve düzenlemelerin yasal sekillerine esasından daha fazla önem veren detaylı kurallara dayalı bir sistemdir. Kıta Avrupası muhasebe gelenegini takip eder. Öte yandan UFRS geleneksel bir sekilde ilkelere dayalı, az detaycı bir sistemdir ve ekonomik gerçeklige önem verir. UFRS büyük ölçüde Anglo Amerikan geleneginde gelisen milletler üstü standartlardır. Çalısmamda, finansal varlık ve finansal yükümlülüklerin ölçümlemesinde UFRS ve AGKGM_ farklarının üzerinde durulmustur. Bu detaylı analiz, finansal varlık ve finansal yükümlülüklerin kapsam, sınıflandırma, tanıma, bilanço dısına çıkarılma, ölçümleme ve mahsup yönlerinden farklarını içermektedir. Uygulama bölümünde yakınsama projesinin en önemli bölümü olarak kabul edilen, Amerika Sermaye Piyasası Kurulu tarafından yabancı yatırımcılardan istenen, 20-F raporu mutabakatlarına deginilmektedir. Hayali bir firmaya ait finansal varlık ve finansal yükümlülükler için 20-F raporu mutabakat sartları ayrıntılı olarak incelenmistir. MEASUREMENT OF FINANCIAL ASSETS AND FINANCIAL LIABILITIES: IFRS/ US GAAP COMPARISON The differences between rules of financial reporting in different countries cause complexity in accounting. For the international globalization, the diversity in accounting should be minimized and harmonization should be achieved. National standards in most countries of the world have been based mostly on either IFRS or US GAAP. The logical solution to form a single set of global accounting standards in a reasonable time is to work toward convergence of IFRS and US GAAP, which will affect those countries that continue to maintain their national GAAP. The main obstacle for the convergence project is that IFRS and US GAAP are two fundamentally different systems of financial reporting. US GAAP is a detailed rules-based system that gives importance to the legal form of transactions and arrangements over the economic substance. US GAAP follows the Continental European accounting tradition. On the other hand; IFRS have traditionally been principles-based and less detailed and gives importance to economic reality. IFRS are supranational standards developed largely in Anglo American tradition. In my study, I addressed the IFRS and US GAAP differences in measuring financial assets and financial liabilities. The detailed comparison includes differences in scope, classification, recognition, derecognition, measurement and offsetting of financial assets and financial liabilities. The application part of my thesis deals with one of the most important parts of the convergence project the 20-F reconciliation that is required by SEC from foreign investors. The 20-F report reconciliation requirements for financial assets and financial liabilities of a fictitious entity are analyzed in details.
Keywords: Standartlar_Finansal Tablolar; Varlık_Muhasebe